New snakeflies (Insecta: Raphidioptera: Mesoraphidiidae) from the Lower Cretaceous Sinuiju Formation of the Democratic People's Republic of Korea. (April 2022) - Ri, Chol-Jun; Won, Chol-Guk; So, Kwang-Sik; Ho, Myong-Sik
Abstract: Two fossil snakeﬂy specimens from the Lower Cretaceous (Barremian–Aptian) of the Sinuiju Formation in Sinuiju City, DPRK are described and figured. They are considered as the first representatives of two new species, namely: Mesoraphidia ryonsangensis sp. nov. and M. baekthoensis . sp. nov. and placed in the family Mesoraphidiidae. These descriptions increase the diversity of snakeflies from the Lower Cretaceous. Highlights: Two new fossil snakeﬂy species from the Sinuiju Formation were firstly discovered. They are Mesoraphidia ryonsangia and M. baekthoensis. They belong to family Mesoraphidiidae (Insecta: Raphidioptera). These increase the diversity of snakeflies from the Lower Cretaceous.